Pengaruh Program Pelayanan SAMSAT, Insentif Pajak dan Kesadaran Pajak Terhadap Tingkat Kepatuhan Pembayaran Pajak Kendaraan Bermotor pada SAMSAT Kota Gorontalo - Putra Mahmud; Ayu Rakhma Wuryandini; Nurharyati Panigoro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The aim of this research is to determine the effect of the Samsat service program, tax incentives and tax awareness on the level of compliance with motor vehicle tax payments in Gorontalo City Samsat. The type of method used in this research is a quantitative method with data collection techniques using questionnaire surveys and observation. The number of respondents in this study was 100 respondents consisting of motor vehicle taxpayers registered with the Gorontalo City Samsat. The tool used in this research uses multiple linear regression analysis. The research results show that 1. The Samsat service program has a positive and significant effect on the level of compliance with motor vehicle tax payments. 2. Tax incentives have a positive and significant effect on the level of compliance with motor vehicle tax payments. 3. Tax awareness has a positive and significant effect on the level of compliance with motor vehicle tax payments. 4. Simultaneously, the Samsat service program, tax incentives and tax awareness have a positive effect on the level of compliance with motor vehicle tax payments.